The guest in Room 120 : a novel - Ackerman, Sara (Mira, 2025)
"1905. As the mother of a university and a woman with an iron will, Jane Stanford has made her share of enemies. After a scare at hermansion in San Francisco and on the advice of her doctor, she fleesto Honolulu and the fashionable new Moana hotel. But as fate would have it, the island is not as safe as it seems. 2005. Zoe Finch is a bestselling author who desperately needs a jump start on her next novel, and she makes a split decision to attend a writers' conferenceat the Moana under an assumed name. As a storm brews offshore, she begins having nightmares that feel hauntingly real. Terrified, Zoe enlists the help of mystery writer Dylan Winters and, over the courseof the week, races to uncover the shocking truth of what happened in the hotel one hundred years ago almost to the day. 1905. 'Iliahi Baldwin's life changes the moment she lands a job at the Moana. Newlyhired and reeling from a tragic loss, she strikes up an unlikely friendship with the formidable Jane Stanford upon her arrival, which leaves young 'Ili devastated when the unthinkable happens. 'Ili knowsthings, but there are powerful people who need the truth to remain hidden, and to cross them could prove disastrous. Inspired by the incredible true story of one of America's most mysterious deaths, thisis an unforgettable tale of betrayal and secrets that still echoes through the years."--Provided by publisher.